Cross-cultural communication experiences among international sojourners in Malaysian universities / Massila Hamzah - Hamzah, Massila (2014)
This qualitative study focuses on cross-cultural communication experiences among international sojourners (IS) in Malaysian universities. Four research objectives were addressed : 1) to identify the transition shock symptoms in cross-culture communication faced by the international sojourners in Malaysian universities, 2) to determine the building blocks faced by international sojourners in cross-cultural transition, 3) to identify the aspects of perceived similarities or differences by international sojourners in their manifestations of culture 4) to ascertain the adaptation strategies embraced by international sojourners in overcoming cross-cultural communication challenges. Salient discoveries were obtained through in-depth interview with fifteen IS residing in Malaysian universities. The findings painted a vivid picture of the sojourning experiences. Firstly, the symptoms of transition shock were highly characterized by initial sojourning experiences, home separation struggles, emotional distress, initial communication-related stress and acclimatizing to surrounding. Initial sojourning anticipations contributed to themes of: i) unexpected encounters ii) felt differences iii) influences of past experiences. Home separation verify various struggles along the themes of : i) homesickness, ii) attachment need and iii) nostalgic feeling. Indications of emotional distress derived to themes of: i). affective upheavals, ii) yearning to leave and iii) challenged by strangeness. Initial communication-related symptom were salient in themes of : i) initial engagement challenges ii) interaction gap, and iii) withdrawal. Acclimatizing to the surroundings contributed to themes of : i) weather condition, and ii) food acceptance. Secondly, findings warranted the building blocks in cross-culture transition were associated to communication tribulations, language barriers and cross-cultural disputes. Communication tribulations contributed to themes of : i) predicaments in forming relationships, ii) arousing suspicion iii) nonverbal cues. Language barriers derived to themes of : i) interaction difficulties, ii) code substitute and iii) differences in the representation of meanings and pronunciation. Cross-cultural disputes persists in themes of: i) adapting to differences, ii) treatment against IS, iii) socially inappropriate behavior. Thirdly, aspects of perceived similarities or differences were manifested in value orientation and, cultural norms and rules. The themes were associated with : i) familial attachment, ii) society conformity and iii) interpersonal engagement. Likewise, cultural norms and rules subscribed to themes of i) appropriate standards of behavior and ii) attitude towards time and work commitment. Fourth, the strategies to overcome cross-cultural communication challenges were adjustment approach, cross-cultural resilience approach and passive-defensive approach. The adjustment approach uncovered four emerging themes: i) seek balance while preserving cultural identity, ii) negotiating cultural differences, iii) building relationships through communication and iv) local language acquisition. Cross cultural resilience approach contributed to themes of: i) receptive personality, ii) managing cross-cultural adversities and iii) avoid being judgmental. Passive defensive approach revealed two salient themes of : i) submission to circumstance and i)seeking shared-group support. In conclusion, across the nexus of cultural diversity lies the challenge to fathom the nuances between home and host culture. Nonetheless, regardless of various ramifications, making adjustments to attain cross-cultural liberation demonstrated a life-changing journey and a rewarding experience.